2018
DOI: 10.31234/osf.io/6fjr7
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Do smartphone usage scales predict behavior?

Abstract: Understanding how people use technology remains important, particularly when measuring the impact this might have on individuals and society. However, despite a growing body of resources that can quantify smartphone use, research within psychology and social science overwhelmingly relies on self-reported assessments. These have yet to convincingly demonstrate an ability to predict objective behavior. Here, and for the first time, we compare a variety of smartphone use and ‘addiction’ scales with objective beha… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
123
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(133 citation statements)
references
References 0 publications
10
123
0
Order By: Relevance
“…Empirically, the assessment of problematic media use is hindered by unresolved theoretical and etiological foundations, as well as general challenges in assessing media use [6]. Adopting a tendency present in much of modern Social Psychology [4], researchers have relied on retrospective self-report questionnaires (or scales) to assess individuals' propensities for various behaviours, disorders, or other related outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Empirically, the assessment of problematic media use is hindered by unresolved theoretical and etiological foundations, as well as general challenges in assessing media use [6]. Adopting a tendency present in much of modern Social Psychology [4], researchers have relied on retrospective self-report questionnaires (or scales) to assess individuals' propensities for various behaviours, disorders, or other related outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Johannes et al (in press) found that receiving a notification during a cognitive control task did not impair performance despite participants reporting to find the notification highly distracting. In a similar vein, other studies found that people are not good estimators of their own smartphone or internet use (Ellis, Davidson, Shaw, & Geyer, 2018;Scharkow, 2016). Taken together, these findings suggest that there might be a gap between what people themselves report about the distractions of their smartphones and the actual behavioral impairment these devices exert on them.…”
Section: Discussionmentioning
confidence: 64%
“…While weak correlations have been shown for a number of scales for both smartphone use in general and addiction in particular, and more objective assessments of media use [6], this does not necessarily imply that scales purporting to assess problematic behaviours are invalid or spurious -use is only one component of the behavioural and mental patterns targeted. Nevertheless, in a review of 45 tools designed to assess Internet addiction, Laconi et al [15] found that only 26 had been evaluated for their psychometric properties.…”
Section: Introductionmentioning
confidence: 96%
“…Empirically, the assessment of problematic media use is hindered by unresolved theoretical and etiological foundations, as well as general challenges in assessing media use [6]. Adopting a tendency present in much of modern Social Psychology [4], researchers have relied on retrospective self-report questionnaires (or scales) to assess individuals' propensities for various behaviours, disorders, or other related outcomes.…”
Section: Introductionmentioning
confidence: 99%